2006
DOI: 10.4049/jimmunol.177.8.5328
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Binds Different CD43 Glycoforms to Cluster CD43 and Regulate T Cell Death

Abstract: Galectin-1 kills immature thymocytes and activated peripheral T cells by binding to glycans on T cell glycoproteins including CD7, CD45, and CD43. Although roles for CD7 and CD45 in regulating galectin-1-induced death have been described, the requirement for CD43 remains unknown. We describe a novel role for CD43 in galectin-1-induced death, and the effects of O-glycan modification on galectin-1 binding to CD43. Loss of CD43 expression reduced galectin-1 death of murine thymocytes and human T lymphoblastoid ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 63 publications
3
99
0
1
Order By: Relevance
“…Changes in the glycosylation pattern of its extracellular domain allow CD43 to function as a proadhesive counter receptor for galectin-1, ICAM-1, E-selectin, sialoadhesin and MHC Class I molecules. 16,23,[25][26][27][28]37,39,40 While CD43 is normally restricted in its expression to leukocytes and platelets, aberrant expression has been consistently described in colon and salivary gland cancers. [41][42][43][44] In addition, limited analysis suggested that NSCLC but not SCLC might also be characterized by CD43 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the glycosylation pattern of its extracellular domain allow CD43 to function as a proadhesive counter receptor for galectin-1, ICAM-1, E-selectin, sialoadhesin and MHC Class I molecules. 16,23,[25][26][27][28]37,39,40 While CD43 is normally restricted in its expression to leukocytes and platelets, aberrant expression has been consistently described in colon and salivary gland cancers. [41][42][43][44] In addition, limited analysis suggested that NSCLC but not SCLC might also be characterized by CD43 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This multivalency also allows the formation of lectin-carbohydrate lattices. Both in solution and on the cell surface, multivalent galectins selectively cross-link a single species of glycoprotein to form homogeneous lectin-carbohydrate lattices [5,17,19].…”
Section: Biochemical Aspects Of Galectin-glycoprotein Lattices Formationmentioning
confidence: 99%
“…Galectin-1, -2, -3 and -9 bind distinct cell surface glycoprotein receptors and trigger distinct intracellular signaling pathways to promote T-cell death [17,19,[35][36][37]. Remarkably, a number of factors determine the responsiveness of cells to galectin-mediated signals which include the repertoire of glycosylated molecules expressed on the cell surface and the activities of specific glycosyltransferases, which are responsible for creating or masking galectin ligands [5,6,18].…”
Section: Galectin-glycoprotein Lattices In T Cell Functionsmentioning
confidence: 99%
“…2 These glycoproteins can display a variety of carbohydrate epitopes, making them versatile participants in cellular recognition. The variation of the pendant carbohydrate epitopes reflects cell development and condition, [3][4][5] contributing to the modulation of cell-cell interactions, as well as mediating cellular responses to other proteins in the extracellular milieu through effects on localization of the cytoplasmic portions of these cell surface molecules. 3 Such glycoproteins also present potential therapeutic targets particularly in tumor cells, 6 being set apart by aberrant mucin protein glycosylation.…”
Section: Introductionmentioning
confidence: 99%